Nutritional evaluation of rain tree (Samanea saman) pod and its incorporation in the diet of rohu (Labeo rohita Hamilton) larvae as a non-conventional feed ingredient - Rath, Suresh Chandra; Nayak, K. C.; Mohanta, K. N.; Pradhan, C.; Rangacharyulu, P. V.; Sarkar, S.; Giri, S. S. (Indian Journal of Fisheries, 2014)
Rain tree (Samanea saman) pod (RTP) is identified as a good source of protein (25.2%) and energy (20.4 kJ g-1) for carp feed. In the present study, RTP as a non-conventional feed ingredient was tested for the first time in carp feeds. Five iso-nitrogenous (25% crude protein) feeds were formulated by incorporating RTP at 0 (F1), 100 (F2), 200 (F3), 300 (F4) and 400 (F5) g kg -1 as co-ingredient, partially substituting groundnut oil cake and rice bran. Feeds were fed to Labeo rohita larvae ad libitum for 30 days in FRP flow-through tanks. The survival of the larvae was higher (87 – 90%) in F1- F4, but it reduced significantly (61%, p< 0.05) in F5. Weight gain (%) and specific growth rate (SGR) were significantly higher (p<0.05) in F4 and F5 groups and food conversion ratio (FCR) was significantly lower (p<0.05) in F4. Protein efficiency ratio (PER) and net protein utilisation (NPU) were found significantly higher (p<0.05) in F4. The results indicated that RTP can be incorporated at 300 g kg-1 substituting 25% groundnut oil cake and 42% rice bran in the diet of L. rohita larvae without any adverse effect on growth, survival and nutrient utilisation.